Do Earnings Targets and Managerial Incentives Affect Sticky Costs? - KAMA, ITAY; WEISS, DAN (Journal of Accounting Research, 2013)
ABSTRACT This study explores motivations underlying managers’ resource adjustments. We focus on the impact of incentives to meet earnings targets on resource adjustments and the ensuing cost structures. We find that, when managers face incentives to avoid losses or earnings decreases, or to meet financial analysts’ earnings forecasts, they expedite downward adjustment of slack resources for sales decreases. These deliberate decisions lessen the degree of cost stickiness rather than induce cost stickiness. The results suggest that efforts to understand determinants of firms’ cost structures should be made in light of the managers’ motivations, particularly agency‐driven incentives underlying resource adjustment decisions.